Relationships between Foreign Language Sound Perception and Production and Experimental Evidences Obtained in Thai Native Speakers - Na Ayudhya, Sudasna; Panornuang, (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this article is to discuss the issues concerning the relationships between foreign sound perception and production. The relationships between foreign sound perception and production are complex, and there are two controversial findings: perception precedes production or vice versa. The assumption of perception precedes production, which was originally proposed by Polivanov (1931), claiming that perception of a new phonetic contrast must necessarily precede its production. Whereas the assumption of production precedes perception, it points out that in certain cases, the production of FL sounds might precede their perception (Neufeld, 1988; Borrell, 1990). This paper will provide the comparison of these two assumptions as well as the experimental evidence of relationships between perception and production in foreign language based on a finding of error rate analysis obtained from English voicing perception task and production task in 200 Thai native speakers.